Devonian alkaline magmatism in the northern North China Craton: Geochemistry, SHRIMP zircon U-Pb geochronology and Sr-Nd-Hf isotopes - Dingling Huang (Geoscience Frontiers, 2017)
The Wulanhada pluton is among the rare suite of Devonian alkaline plutons occurring along the northern margin of the North China Craton (NCC). The intrusion is mainly composed of quartz-monzonite. Here we report zircon SHRIMP U-Pb data from this intrusion which shows emplacement age of ca. 381.5 Ma. The rock is metaluminous with high (Na2O + K2O) values ranging from 8.46 to 9.66 wt.%. The REE patterns of the rocks do not show any Eu anomaly whereas the primitive-mantle-normalized spider diagram shows strong positive Sr and Ba anomalies. The Wulanhada rocks exhibit high initial values of (87Sr/86Sr)t = 0.70762–0.70809, low ɛNd(t) = −12.76 to −12.15 values and negative values of ɛHf(t) = −23.49 to −17.02 with small variations in (176Hf/177Hf)t (0.281873–0.282049). These geochemical features and quantitative isotopic modeling results suggest that the rocks might have been formed through the partial melting of Neoarchean basic rocks in the lower crust of the NCC. The Wulanhada rocks, together with the Devonian alkaline rocks and mafic-ultramafic complex from neighboring regions, constitute a post-collisional magmatic belt along the northern NCC.